Menyoal Konsep Penandingan dalam Perspektif Budaya - Beatrix Yunarti Manehat; Yolinda Yanti Sonbay; Viany Cecilia Pah (Jurusan Akuntansi Politeknik Negeri Malang, 2022)
This study aims to photograph the reality of the matching concept in the faken culture in death, the meaning of faken, and the basis for its determination in the Uma Duakun Fauleon Tribe, Belu-NTT. The transcendental phenomenology method was used in this study. The results show that the matching concept in the business world is different from the practice in indigenous peoples. There is no revenue claim for the costs incurred for the faken at the time of death. Faken symbolizes appreciation and support for the deceased. Acceptance of the awareness of mutual help is reflected in the faken. The traditional fortune regulates the loading of faken. The party responsible for paying the faken is the sister. The basis for determining faken is the closeness of family relationships. Abstrak Penelitian ini bertujuan untuk memotret realita konsep penandingan (matching) dalam budaya faken di kematian, makna, serta dasar penetapannya di Suku Adat Uma Duakun Fauleon, Belu-NTT. Metode fenomenologi transcendental digunakan dalam penelitian ini. Hasil penelitian menunjukkan bahwa konsep matching yang ada di dunia bisnis berbeda dengan praktik di masyarakat adat. Tidak ada tuntutan pendapatan atas biaya yang telah dikeluarkan untuk faken saat kematian. Penerimaan atas kesadaran saling membantu tercermin dalam faken. Tuah adat mengatur pembebanan faken. Pihak yang bertanggungjawab untuk membayar faken adalah saudari perempuan. Dasar penetapan faken adalah kedekatan hubungan keluarga.